Study on Pattern Design Method of Women Tight Skirts Based on 3D Point-cloud Data (Journal of Fiber Bioengineering and Informatics, 2012)
In this research, 100 female students aged from 18 to 24 years old were selected to take part in thebody measurement. Data acquisition software named Imageware with a 3D scanner was employed togain the body point-cloud diagram. Then, the characteristics of the young female lower body torso havebeen analyzed according to the data obtained. The regression of the key parts of women skirts and thecharacteristics of young female lower body torso has been found. Finally, the generating rules of thebasic pattern of women skirts were established, which provides the foundation for auto-generation ofskirt pattern.